18th International Parallel and Distributed Processing Symposium, 2004. Proceedings.
DOI: 10.1109/ipdps.2004.1303123
|View full text |Cite
|
Sign up to set email alerts
|

Designing a runtime reconfigurable processor for general purpose applications

Abstract: A superscalar microprocessor with a variable number of execution units which are dynamically configured during program execution has been modeled. The runtime behaviour of an executed application is determined using a Trace Cache and the most suitable hardware configuration is loaded dynamically. This paper discusses major design aspects of the ongoing implementation process based on a partial reconfiguration design flow. Thus, some microarchitectural components are put together to form a fixed module while di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In [16], it is shown that the reconfigurable coprocessor speeds up the architecture by 190 for a specific application (EEMBC). A similar approach is proposed in [17] where the authors define a complete reconfigurable core for the processor. The instruction set of the architecture is fixed but the core of the processor has different configurations for the ALU.…”
Section: ) Dedicated Processorsmentioning
confidence: 99%
“…In [16], it is shown that the reconfigurable coprocessor speeds up the architecture by 190 for a specific application (EEMBC). A similar approach is proposed in [17] where the authors define a complete reconfigurable core for the processor. The instruction set of the architecture is fixed but the core of the processor has different configurations for the ALU.…”
Section: ) Dedicated Processorsmentioning
confidence: 99%
“…With these definitions, the number of unique combinations is equal to the number of nonnegative integer solutions to Equation (1), which is expressed in component form in Equation (2). As stated earlier, we assume a minimal RFU size of unity, which implies that all combinations are complete in the sense that "wasted space," does not exist.…”
Section: Configuration Space Complexitymentioning
confidence: 99%
“…The architecture assumed in this paper is similar to that presented in [1] and originally proposed in [2]. This architecture is partially run-time reconfigurable at the level of reconfigurable functional unit (RFU) "slots".…”
Section: Introduction and Related Workmentioning
confidence: 99%
See 1 more Smart Citation